INFLUENCE OF SIZE, STATION TIME AND SATIATION AMOUNT ON PREY HANDLING TIME IN ANABAS TESTUDINEUS (BLOCH) - ARAVINDAN, C. M.; SREEKUMARI, T. (Journal of Indian Fisheries Association, 2015)
Satiation amount, satiation time and handling time of Anabas testudineus (Bloch), an airbreathingpredatory fish was experimentally estimated using guppy (Lebistes reticulatus) asprey. Weight of the fish and satiation time influenced prey handling time. As satiation time isrelated to the level of hunger, level of hunger was found to influence handling time of prey.